Metabolites as regulators of autoimmune diseases - Tada, Maria; Kono, Michihito (Frontiers in Immunology, 2025)
Immune cell metabolism is essential for regulating immune responses, including activation, differentiation, and function. Through glycolysis and oxidative phosphorylation (OXPHOS), metabolism supplies energy and key intermediates for cell growth and proliferation. Importantly, some metabolites generated during these processes act as signaling molecules that influence immune activity. Autoimmune diseases such as rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE) involve multiple immune cell types, and recent research in immunometabolism has revealed that disrupted metabolic pathways in these cells contribute to disease progression. Effector T cells, for instance, undergo metabolic reprogramming, particularly increased glycolysis, to meet the demands of proliferation and function during autoimmune responses. Targeting metabolic enzymes has shown therapeutic potential. In addition, metabolites themselves, termed immunometabolites, can directly modulate immune responses. These include both intracellularly generated and secreted molecules. Itaconate is a key immunometabolite and is derived from the TCA cycle by aconitate decarboxylase 1 (ACOD1) in activated macrophages. It inhibits the NLRP3 inflammasome and pro-inflammatory cytokines, such as IL-1β and IL-6. Beyond macrophages, itaconate alters metabolism and epigenetics in T cells by reducing 2-hydroxyglutarate and the S-adenosyl-L-methionine (SAM)/S-adenosyl-L-homocysteine (SAH) ratio, thereby suppressing Th17 differentiation and enhancing Foxp3 expression in Tregs. Itaconate ameliorates disease in experimental autoimmune encephalomyelitis, RA, SLE, and others. It also exhibits antimicrobial effects by blocking bacterial isocitrate lyase and viral replication. Despite increasing interest, reviews focusing specifically on immunometabolites remain limited. This review highlights emerging insights into metabolites involved in glycolysis, the TCA cycle, glutaminolysis, one-carbon metabolism, and lipid metabolism that influence autoimmune pathophysiology.